Edukasi Manajemen Stres dalam Peningkatan Pengetahuan Ibu Rumah Tangga di Desa Mandirancan Kuningan - Latifah, Riza Arisanty (Universitas Baiturrahim, 2024)
Being a housewife is a choice. Housewife is a profession that requires someone to work 24 hours a day. This can trigger a mother to experience stress either because of monotonous activities, because there is no end to work or lack of rest. This trigger stresses. Stress can be prevented with non-pharmacological stress management, one of which is the progressive muscle relaxation technique, but many mothers do not know this technique so the author is interested in providing education about stress management to housewives in Mandirancan Village, Kuningn. The purpose of this education is so that housewives can prevent and handle it. This method is through education and direct demonstration of how to manage stress with progressive muscle relaxation which was carried out on June 22, 2024 in Mandirancan Village, which was attended by 46 housewives. The demonstration was carried out immediately after the material was completed. Progressive muscle relaxation was carried out for 1 meeting which was then continued with a redemotion by all participants. The results of this education were that most housewives were able to directly demonstrate the progressive muscle relaxation technique and some could feel the benefits. Based on the measurement of the level of knowledge, the pre-test results showed that the knowledge was lacking by 32 IRT and good knowledge by 14 IRT and for the post-test results; the knowledge was lacking by 9 IRT and good knowledge by 37 IRT. The conclusion is that there is an increase in the knowledge of housewives before and after being given education. Suggestions for housewives can use progressive muscle relaxation therapy when signs and symptoms of stress begin to appear.